Lectura crítica de los procedimientos estadísticos aplicados en el campo de la psicología - Rondini, Carina Alexandra [UNESP]; Souza Paulillo, Thais [UNESP]; Suzano Martinhão, Viviane; Molica Marinheiro, Bianca [UNESP]; Aragão Martins, Raul [UNESP] (Colegio Mayor de Nuestra Senora del Rosario, 2016)
We present a critical analysis of the use and application of statistics in scientific articles in psychology, pointing out the main difficulties of its applicability. Searching the database Virtual Health Library VHL Psychology ULAPSI Brazil and using the Keywords Statistics and Psychology, we found 24 articles that adopted basic statistics to collect and analyze your data. Through literature research and content analysis, we identified possible gaps in the employment of Statistics, noting the items: correct definition of the sample / population, presentation and justification of the chosen statistical tests, correct use of appropriate tests and analysis of results. We found that 21 articles no failed to present at least one relevant statistical information; 9 clearly showed the sample; 9 defined a statistical method for the analysis of the results and justifed its use; 12 did not describe the method used; 18 made their analyzes correctly. Inadequate and / or inefficient adoption of statistics can lead to hasty or even erroneous conclusions from the results. A careful and thoughtful use of statistics provides a coherent scientific production and responsible with the studied facts.
Leitura crítica dos procedimentos estatísticos aplicados no campo da psicologia
Critical reading of statistical procedures applied to the field of psychology
Keywords: Critical reading; Psychology; Statistics applied psychology